2022
DOI: 10.3389/fphar.2022.854249
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Quercetin on Ischemic Stroke: A Literature Review

Abstract: Ischemic stroke (IS) is characterized by high recurrence and disability; however, its therapies are very limited. As one of the effective methods of treating acute attacks of IS, intravenous thrombolysis has a clear time window. Quercetin, a flavonoid widely found in vegetables and fruits, inhibits immune cells from secreting inflammatory cytokines, thereby reducing platelet aggregation and limiting inflammatory thrombosis. In pre-clinical studies, it has been shown to exhibit neuroprotective effects in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 168 publications
(170 reference statements)
0
21
0
Order By: Relevance
“…Quercetin, a plant flavonoid, has antioxidant, anti-fibrotic, anti-inflammatory, anti-cancer and neuroprotective effects ( Ozsoy Gokbilen et al, 2022 ; Zhang et al, 2022 ). A previous study found that resveratrol/quercetin induced activation of SIRT1, resulting in the induction of p53 deacetylation.…”
Section: Therapeutic Approaches In Sepsis-induced Acute Kidney Injurymentioning
confidence: 99%
“…Quercetin, a plant flavonoid, has antioxidant, anti-fibrotic, anti-inflammatory, anti-cancer and neuroprotective effects ( Ozsoy Gokbilen et al, 2022 ; Zhang et al, 2022 ). A previous study found that resveratrol/quercetin induced activation of SIRT1, resulting in the induction of p53 deacetylation.…”
Section: Therapeutic Approaches In Sepsis-induced Acute Kidney Injurymentioning
confidence: 99%
“…Quercetin glycosides are found in higher circulating concentrations, hypothesized to be due to sodium-dependent glucose transporters in the GI epithelium [ 38 ]. Although quercetin and its metabolites have been studied and calculated in circulation, it has been observed that quercetin’s bioavailability is too low for quercetin’s health benefits to take effect in the brain, especially given that the blood–brain barrier is impermeable to quercetin [ 40 ]. Therefore, overcoming quercetin’s low bioavailability and half-life will be critical in the application of its beneficial in vivo effects to attenuating GE.…”
Section: Quercetinmentioning
confidence: 99%
“…Many of the cellular conditions during GE activate apoptotic mechanisms by various methods, most of which can be counteracted by quercetin, as seen in Figure 4 , showing quercetin to be a beneficial therapy against GE. Firstly, quercetin has been shown to upregulate PI3K/AKT pathways in ischemic rat cells, leading to decreased expressed, apoptotic caspase 3 enzymes [ 40 ]. Quercetin can direct inhibition and downregulation of caspase 3 activation, which protects cells from intrinsic apoptosis mechanisms [ 56 , 57 , 58 , 59 ].…”
Section: Quercetinmentioning
confidence: 99%
See 2 more Smart Citations